Experimental and Simulative Analysis of Magnetic Nanoparticle Accumulation Using Various Halbach Arrays - Thalmayer Angelika S.; Götz Kilian; Lübke Maximilian; Fischer Georg (Current Directions in Biomedical Engineering)
One of the major challenges in using magnetic nanoparticles in biomedical applications is still the accurate steering and trapping of these particles at a desired location, like at a tumor. Halbach arrays are well-established here as they generate the strongest magnetic force. However, these arrays are mechanically unstable, and thus, their potential to attract magnetic particles is often investigated fully numerically. Hence, this paper provides instructions on how to easily produce Halbach arrays using permanent magnets and metal glue. In total, three Halbach arrays of five, seven, and nine magnets were produced and analyzed regarding their potential for capturing magnetic particles in a background flow, numerically using COMSOL Multiphysics and in measurements. Furthermore, the Halbach arrays are compared with two other array configurations with all magnetizations in the same directions and alternating once. Overall, the simulation results were in good agreement with the measurement results. The amount of captured particles was significantly higher in measurements for the Halbach arrays with 8.2 %, compared to the array with alternating magnetization direction with 6.6% captured particles. Therefore, using Halbach arrays to capture or steer magnetic nanoparticles in a background flow is strongly recommended.